2016
DOI: 10.1038/srep36739
|View full text |Cite
|
Sign up to set email alerts
|

Effect of p22phox depletion on sympathetic regulation of blood pressure in SHRSP: evaluation in a new congenic strain

Abstract: Oxidative stress in the rostral ventrolateral medulla (RVLM), a sympathetic center in the brainstem, was implicated in the regulation of sympathetic activity in various hypertensive models including stroke-prone spontaneously hypertensive rats (SHRSP). In this study, we evaluated the role of the NADPH oxidases (NOX) in the blood pressure (BP) regulation in RVLM in SHRSP. The P22PHOX-depleted congenic SHRSP (called SP.MES) was constructed by introducing the mutated p22phox gene of Matsumoto Eosinophilic Shinshu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…The RVLM was chemically identified by a pressor response (>20 mmHg) to L-glutamate (1 nmol) microinjection. The changes in BP, HR, and renal sympathetic nerve activity (RSNA) were recorded 10 min after injection of Tempol (5 nmol), which was based on the previous study (Wang et al, 2016 ; Zahid et al, 2016 ). At the end of each experiment, 100 nl of 2% pontamine sky blue solution was injected into the RVLM to mark the site.…”
Section: Methodsmentioning
confidence: 99%
“…The RVLM was chemically identified by a pressor response (>20 mmHg) to L-glutamate (1 nmol) microinjection. The changes in BP, HR, and renal sympathetic nerve activity (RSNA) were recorded 10 min after injection of Tempol (5 nmol), which was based on the previous study (Wang et al, 2016 ; Zahid et al, 2016 ). At the end of each experiment, 100 nl of 2% pontamine sky blue solution was injected into the RVLM to mark the site.…”
Section: Methodsmentioning
confidence: 99%
“…Urinary 15-isoprostane-F2t (IsoP) excretion level was measured to estimate oxidative stress [13] using an ELISA kit (JaICA, Nikken SEIL Co., Ltd.). Urinary protein level was determined in 24h urine samples as well with the protein assay BCA kit (Wako Pure Chemical Industries Ltd., Japan) [14]. The measurements were performed according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…These results highlight the complexities regarding the interactions between Nox activity and blood pressure regulation. Furthermore, one of the authors’ group reported that blood pressure response to glutamate microinjection into the rostral ventrolateral medulla was significantly greater in SHRSP than in SP.MES, SHR and WKY, suggesting that higher oxidative stress or Nox activity in the regulatory center of the sympathetic nerve activity in SHRSP [ 87 ].…”
Section: Experimental Models Of Strokementioning
confidence: 99%